System Modelling and Analysis on Stability of Electro-Hydraulic Pressure Regulating System for Shift Actuator including an Accumulator. Issue 10 (2021) - Ren, Yanfei; Xi, Junqiang; Meng, Fei; Ma, Kaiwen
Abstract: The shift actuator of wet clutch adopt an electro-hydraulic pressure regulating system (EHPRS), which play a critical role to shifting quality. Related research shows that the accumulator can improve the stability of output pressure for EHPRS, but its working mechanism and influence law are not clear yet. In this paper, a spring-type accumulator that connected in parallel in the control chamber of EHPRS is studied and analyzed. Firstly, the system mechanism is analyzed; then, the mathematical model and simulation model of system are established; finally, based on the simulation model, the dynamic characteristics of system are analyzed, and the influence of accumulator on the stability performance is revealed. The results show that under the same conditions, the accumulator can significantly reduce the overshoot of output pressure and shorten the stabilization time of output pressure, without affecting the pressure build-up time of output pressure. At the same time, with the increase of accumulator orifice and spring stiffness, the stability of system is significantly improved. It provides reference value for system design.